2016
DOI: 10.1021/acs.jafc.5b05737
|View full text |Cite
|
Sign up to set email alerts
|

Formation of β Polymorphs in Milk Fats with Large Differences in Triacylglycerol Profiles

Abstract: In this study, we characterized the polymorphism of milk fat (MF) with various TAG compositions during isothermal crystallization at 20 °C. TAG composition of MF from seven individual cows was determined using GC-FID and MALDI-TOF MS, and MF polymorphism was studied using X-ray diffraction. Results showed that TAG profile determines the polymorphic behavior of MF. Saturated TAG with carbon numbers 34-38 promoted the formation of α polymorphs, whereas unsaturated TAG with 52-54 promoted the formation of the β p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…The variability within repetitions was lower than 10% (data not shown). [1,21] Other studies on MF TAG have also reported the absence of saturated TAG with 54 carbons [4,14,22] or have reported small relative concentrations of it. Figures S1 and S2, Supporting Information show the spectra of winter and summer MF, respectively.…”
Section: Triacylglycerol Profiling Of Summer and Winter Mfmentioning
confidence: 99%
See 1 more Smart Citation
“…The variability within repetitions was lower than 10% (data not shown). [1,21] Other studies on MF TAG have also reported the absence of saturated TAG with 54 carbons [4,14,22] or have reported small relative concentrations of it. Figures S1 and S2, Supporting Information show the spectra of winter and summer MF, respectively.…”
Section: Triacylglycerol Profiling Of Summer and Winter Mfmentioning
confidence: 99%
“…Until now, about 220 species of TAG ranging from 22 to 54 carbons and with up to six double bonds have been identified in MF. [4] Furthermore, MF TAG profiles are relevant for understanding MF synthesis. For these reasons, bovine MF is considered one of the more complex natural fats.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely recognized that TAG profile determines the physicochemical properties of milk fat [10,11,12,13], which are important for the processing and quality of dairy products. In addition, TAG structure could affect the absorption efficiency of fatty acids by infants [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In the experiments reported in Chapter 2 and 5 of this thesis, this ratio was affected by some of the dietary treatments applied. The TAG profile also affects solid fat content of milk (Tzompa-Sosa et al, 2016b). From a milk processing perspective, highly unsaturated milk fat with a low C16:0/C18:1cis-9 ratio is less desired.…”
Section: Effect On Milk Processing Parametersmentioning
confidence: 99%
“…Solid fat is an important processing parameter, because it positively influences sensory perception, functionality and structure of fat-rich foods (e.g. muffins, puff pastry, ice cream) (Tzompa-Sosa et al, 2016b). The alteration in milk FA profile towards more unsaturated fatty acids upon feeding DHA is, therefore, desirable from a human health perspective, but not from a processing perspective.…”
Section: Effect On Milk Processing Parametersmentioning
confidence: 99%